Nutritional and Zinc Levels in Serum and Hair of University Students in Nigde, Turkey - ALAN OZTURK, ZEYNEP; BATTALOGLU, RIFAT; KAYAKIRILMAZ, KADRIYE; AKSOY, MERAL; BAYOL, EMEL (Asian Journal of Chemistry, 2010)
This research has been designed for the determination of the nutritional status of university students, in particular reference to dietary zinc amount taken. The aim was to find out reflection of dietary zinc to that of serum and hair zinc contents. Forty volunteers' students of Nigde University (24 females and 16 males) participated in the first step of research. Three years later, 17 females and 10 males from this group participated for the second stage of research. Students' nutritional status was evaluated according to their food consumption and physical examination. After analyzing the collected blood and hair samples, the mineral status was also evaluated. At the two steps of research no one had any serious mineral and other nutrients deficiencies. Only one female student having mineral deficiency at the first step of work recovered after the treatment. Regression analysis showed that there was a statistically significant correlation between dietary zinc concentration and hair and serum mineral levels (rdiet-hair = 0.500, n = 40, p < 0.01, rdiet-serum = 0.470, n = 40, p < 0.01).